2005
DOI: 10.5194/acp-5-345-2005
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence from atmospheric aerosol detected by a lidar indicates biogenic particles in the lowermost stratosphere

Abstract: Abstract. With a lidar system that was installed in Lindenberg/Germany, we observed in June 2003 an extended aerosol layer at 13 km altitude in the lowermost stratosphere. This layer created an inelastic backscatter signal that we detected with a water vapour Raman channel, but that was not produced by Raman scattering. Also, we find evidence for inelastic scattering from a smoke plume from a forest fire that we observed in the troposphere. We interpret the unexpected properties of these aerosols as fluorescen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…(Solberg et al, 2008), and surface aerosol characterization, e.g. (Immler et al, 2005;Pace et al, 2005). These papers suggest a potential impact of Portuguese forest fires over northern Europe.…”
Section: Biomass Burning Co Emissionsmentioning
confidence: 87%
“…(Solberg et al, 2008), and surface aerosol characterization, e.g. (Immler et al, 2005;Pace et al, 2005). These papers suggest a potential impact of Portuguese forest fires over northern Europe.…”
Section: Biomass Burning Co Emissionsmentioning
confidence: 87%
“…Eventually, the whole concept of "light-absorbing carbon", and the analytical methods used, need to be carefully reconsidered and "standardized" to provide reliable input for atmospheric models and legislative measures. Novel measurement techniques, such as the use of fluorescence lidar (Immler et al, 2005), spectral absorption measurements (Kirchstetter et al, 2004), and Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS) (Kramer et al, 2004), will have to be applied to determine the concentrations, distribution and properties of C brown . The development and widespread use of standard reference materials, such as RM 8785 (Air Particulate Matter on Filter Media) (Klouda et al, 2005) is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Simard et al, 2004;Glennon et al, 2009). The detection of fluorescent ambient aerosol was reported for the first time using a LIDAR system (Immler et al, 2005), attributing the signals to a combination of PAH-containing particles and/or PBAP. Furthermore, it was shown (Sassen, 2008) that pollen can generate strong laser depolarisation in LIDAR backscatter during Alaskan springtime measurements and suggested that pollen plumes may be mistaken for upper cirrus clouds and therefore introduce important errors into identifying aerosols in the atmosphere.…”
Section: Light Detection and Ranging (Lidar) And Remote Sensingmentioning
confidence: 99%